Photovoltaic and EIS Performance of SnO2/SWCNTS Based – Sensitized Solar Cell. (2017) - Abdullah, Huda; Yunos, Nor Haslinda; Mahalingam, Savisha; Ahmad, Masrianis; Yuliarto, Brian
Abstract: Dye-sensitized solar cell (DSSC) is a type of thin film and third generation of photovoltaic devices. In this research, DSSC using tin dioxide/single wall carbon nanotube (SnO2 /SWCNT) was successfully fabricated using doctor blade technique. The objective of this work is to determine the optimum concentration of SWCNT in SnO2 -based DSSC. The thin films were varied with different SWCNT concentrations at 0.1%, 0.2%, 0.3% and 0.4% which acts as photoanode while Pt-Graphene was used as the counter electrode in DSSC. Atomic force microscopy (AFM) determined the surface roughness of the thin films. The pattern of X-ray Diffraction (XRD) shows the thin film's structure and the crystallite size. The Uv-Vis result showed the bandgap of the thin films. The structural (AFM and XRD) and optical (Uv-Vis) analysis were done in order to analyse the factors that influence the performance of the DSSC. The electrochemical impedance analysis was also performed to investigate the electron transport inside the DSSC.